THE CONCEPT OF TIME: A STUDY OF SEMANTIC ANALYSIS AZ-ZAMAN - Ahmad Faqihuddin; Bashori Alwi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Understanding the meaning of the az-zaman and its derivatives has implications not only theoretically (in interpretation, semantics, and theology), but also practically in how humans respond to the times, utilize them, and maintain the relevance of moral values amidst changing times. However, in the literature on interpretation and semantics, in-depth focus on the az-zaman is still limited, especially in contemporary studies that incorporate a modern semantic approach. The method used in this research is library research. This research refers to data derived from various literature such as books, journals, theses, dissertations, and so on. The primary literature in this study is the original text of the Qur'an, classical and contemporary interpretations (Ibn Kathir, Buya Hamka, Quraish Shihab, Al-Azhar interpretation, Al-Misbah interpretation). In semantic studies, the initial step is to refer to the root word as the starting point for basic meaning. The term az‑zaman comes from the Arabic root z–m–n (ز-م-ن). This root is lexically associated with the concepts of masa, time, duration, and temporal transition. This basic meaning is reflected in classical Arabic dictionaries such as Lisan al-Arab, Taj al-‘Arus, and Qamus al-Lughah, where zaman (زمن) is defined as a span of time, masa, era, period, or elapsed time. Time in its etymological sense is something that indicates a specific moment. The Qur’an uses various terms to refer to time, such as al-waqt, al-‘ashr, al-dahr, al-ajal, al-amad, and al-abad. Each term has a different meaning and emphasis. Al-‘ashr indicates the result of feelings or events. Al-amad emphasizes limited time, while al-abad indicates a very long time without limits.